Defect–engineered lithium titanate anode materials for lithium–ion batteries - Podile, Seromo (University of the Witwatersrand, Johannesburg, 2023)
Energy is one of the aspects that plays a central role in moving society forward since it is one of the most important agenda of global economic and energy forums. There is an urgent need to move to clean energy given the environmental and the health benefits resulting from implementing energy systems that utilize green energy. The proposed energy sources in these systems are primarily natural (e.g. wind and solar), which means they are beyond human control and would work better if coupled with energy storage devices (ESDs). From this emerge the importance of energy storage systems (ESSs) which mostly perform based on the materials utilized to assemble the devices. In this study, we seek to enhance the power and energy densities of two of the prominent energy storage systems, namely lithium-ion batteries (LIBs) and lithium-ion capacitors (LICs), using modified commercial lithium titanate (LTO) materials as anodes. The materials consist of the pristine LTO (LTO-p), LTO coated with cerium fluoride (LTO-CeF3) and dry and wet irradiated pristine LTO (LTO-p-md and LTO-p-mw) and LTO coated with cerium fluoride (LTO-CeF3-md and LTO-CeF3-mw). Microwave irradiation was used to study the possible defect that the radiation can bring to the materials and possibly use the microwave effect to improve their electrochemistry. The effects of the coated layer of CeF3 and microwave irradiation on the structure of the commercial LTO were extensively studied using powder X-ray diffractometer (XRD), Raman spectroscopy, transmission electron microscopy (TEM), high resolution transmission electron microscopy (HRTEM), scanning electron microscopy (SEM), Energy-dispersive X-ray spectroscopy (EDS), X-ray photoelectron spectroscopy (XPS), thermogravimetric analysis (TGA) and Brunauer-Emmett-Teller (BET) theory. Structural investigations of TEM micrographs revealed CeF3 was present on the surface of the coated LTO materials. Further analysis did show that some portion of the CeF3 coating layer was co-doped into the LTO nanostructures. The findings from XRD and XPS analyses showed that co doping promoted a mixed state of Ti3+ and Ti4+ resulting from charge compensation when Ce3+ and F possibly substituted Ti4+ and O2-. This mixed state of titanium ions allowed the materials to have high electric conductivity than the pristine LTO (LTO-p). The spectrographs obtained from XPS analysis also showed that LTO microwave irradiated materials without coating experienced the same mixed states, which may have originated from oxygen vacancies that allowed for charge compensation when some of the LTO-p Ti4+ had to turn to Ti3+. The HRTEM analysis demonstrated changes to the lattice planes spacing of the modified LTO materials and these changes supported the (111) lattice plane shifts observed in the XRD analysis. The electrochemistry of the lithium-ion battery was studied on all the materials using cycling voltammetry (CV), galvanostatic charge-discharge (GCD) and electrochemical impedance spectroscopy (EIS) techniques. From GCD technique, the results indicated that the modified materials had higher specific capacities than LTO-p at all rates under rate capability studies. All as prepared materials were stable with coulombic efficiency of almost 100% for 100 cycles using 1 C, with modified materials surpassing LTO-p specific capacity. Cycling at a high rate (5 C) for 1000 cycles, saw LTO-md, LTO-mw, LTO-CeF3 and LTO-CeF3-md having high-capacity degradation after 500 cycles. It was also observed that initial capacities were retained up to the 1000th cycle for LTO-CeF3-mw and LTO-p. With an aim of comparing LTO-p and LTO-CeF3 half cells, these two materials were further studied for lithium-ion capacitors (LICs). This choice was based on LTO-CeF3 having a better charge-discharge profile, high specific capacity and coulombic efficiency than LTO-p. The improvements resulted from the coating layer (leveraging the high ionic conductivity and chemically inert properties of CeF3) and the observed defects seen on the XPS studies created by the coating synthesis process. The LTO-CeF3 anode was paired with a carbon black cathode to construct a full LIC cell. The assembled cell produced a maximal energy density of 107.4 Wh kg 1 with an accompanying power density of 2000 W kg-1, and it yielded a power density of 10 000 W kg -1 with an energy density of 61.8 Wh kg -1.
A dissertation submitted n partial fulfilment of the requirements for the degree of Master of Science (in Chemistry), to the Faculty of Science, School of Chemistry, University of the Witwatersrand, Johannesburg, 2023.
Keywords: Lithium-ion battery; Lithium-ion capacitor; Lithium titanate oxide; Cerium fluoride; Anode; UCTD; SDG-13: Climate action